A Pilot Assessment of New Energy Usage Behaviors: The Impacts of Environmental Accident, Cognitions, and New Energy Policies - Zhang, Jing; Huang, Weilun (Frontiers in Environmental Science, 2022)
Literature reviews and interviews with experts showed that new energy would be the future way of life instead of traditional energy. In this study, a questionnaire survey and SPSS model are used to examine the impacts on people’s new energy usage behavior (NEUB) by its cognitions of energy-related environmental accidents (CEREA) and new energy policies (CNEP), as well as other important factors affecting this behavior. The new energy usage behavior examines people’s new energy usage behavior of product usage (NEUBPU) and forecasted payment (NEUBFP). Among the influencing factors, people’s cognitions of energy-related environmental accidents (CEREA), people’s cognitions of new energy policies (CNEP), new energy characteristics (CNEC), new energy advantages (CNEA), and new energy disadvantages (CNED) are examined, and the influence of personal factors on NEUB is also examined. People’s new energy usage behavior of new energy stove (NEUBNES), new energy car (NEUBNEC), and NEUBFP are significantly positively correlated with CNEP; NEUBNEC is significantly positively correlated with CNEA, and NEUBFP is significantly positively correlated with CNEP and CNED. CNEC and CNEP significantly influence people’s new energy usage behavior of household photovoltaic system (NEUBHPS); CNEP significantly influences NEUBNES; age, monthly income, CNEA, and CNEP significantly influence NEUBNEC; age, monthly income, and CNEP significantly influence NEUBFP.